The position of women workers in the manufacturing. industries in Malaysia - Jamilah Ariffin (Universiti Kebangsaan Malaysia, 1981)
This article examines the present situation of female labour force participation in the manufacturing industries of Malaysia. The discussion centres around three major issues; first, the composition of women workers in the industrial sectors' labour force; second, the employment conditions of industries where majority of women workers are employed; and third, the socio-cultural implications arising from factory employment for women workers in particular and Malaysia society in general.